Efficacy and safety of spesolimab in Asian patients with a generalized pustular psoriasis flare: Results from the randomized, double‐blind, placebo‐controlled Effisayil™ 1 study. Issue 2 (25th October 2022) - Morita, Akimichi; Tsai, Tsen‐Fang; Yee, Evelyn Yap Wen; Okubo, Yukari; Imafuku, Shinichi; Zheng, Min; Li, Ling; Quaresma, Manuel; Thoma, Christian; Choon, Siew Eng
Abstract: Generalized pustular psoriasis is a potentially life‐threatening neutrophilic skin disease characterized by recurrent flares of widespread erythema and eruption of sterile pustules. In the Effisayil™ 1 study (NCT03782792), 53 patients with a generalized pustular psoriasis flare were treated with placebo or spesolimab, a humanized anti‐interleukin‐36 receptor monoclonal antibody, the first targeted treatment to be studied in a randomized clinical trial. Spesolimab treatment resulted in rapid pustular and skin clearance, with an acceptable safety profile. Here, we evaluate the efficacy and safety of spesolimab in 29 Asian patients in the Effisayil™ 1 study. The primary endpoint, a Generalized Pustular Psoriasis Physician Global Assessment (GPPGA) pustulation subscore of 0 (no visible pustules) at Week 1, was achieved by 10 patients (62.5%) randomized to spesolimab and one patient (7.7%) randomized to placebo (risk difference 54.8, 95% confidence interval [CI] 17.3–79.8). The key secondary endpoint, a GPPGA total score of 0 or 1 (clear or almost clear skin) at Week 1, was achieved by eight (50.0%) and two (15.4%) patients, respectively (risk difference 34.6, 95% CI −3.1–64.7). This was similar to previously published data in the overall population in whom the primary and key secondary endpoints were achieved by 54% versus 6% and 43% versus 11% of patients, respectively. The percentages of Asian patients randomized to spesolimab with a GPPGA pustulation subscore of 0 and GPPGA total score of 0 or 1 were sustained above 60% for up to 12 weeks. In these patients, patient‐reported outcomes also improved and markers of systemic inflammation were normalized. Eleven (68.8%) and eight (61.5%) of spesolimab‐ and placebo‐treated patients, respectively, experienced at least one adverse event. In conclusion, spesolimab improved outcomes in Asian patients compared with placebo, supporting its use in the treatment of generalized pustular psoriasis flares.